2016
DOI: 10.1089/aid.2015.0198
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Modified Fourth-Generation Human Immunodeficiency Virus Enzyme Immunoassay for Cross-Sectional Incidence Estimation in Clade B Populations

Abstract: Background: Accurate methods for cross-sectional incidence estimation are needed for HIV surveillance and prevention research. We developed an avidity assay based on the fourth-generation Genetic Systems HIV Combo Ag/Ab EIA (Bio-Rad Combo assay) and evaluated its performance. Materials and Methods: The BioRad Combo assay was modified incubating samples with and without 0.025 M diethylamine (DEA). The avidity index (AI) was calculated as the ratio of the DEA-treated to untreated result for a specific sample. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This misclassification rate is called the false recent rate (FRR) (Welte et al, 2010). Other factors such as low CD4+ T cell count, low viral load, and receiving antiretroviral therapy can also impact the results of serological assays for recent HIV infection and cause misclassification of recent infection (Hladik et al, 2012;Kirkpatrick et al, 2016;Laeyendecker et al, 2012;Longosz et al, 2014). Although technical advances in HIV recency tests have reduced FRR to 1.7% in LAg-EIA, this percentage is still high and may lead to the overestimation of incidence (Barnighausen et al, 2010;Guy et al, 2009;Shah et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This misclassification rate is called the false recent rate (FRR) (Welte et al, 2010). Other factors such as low CD4+ T cell count, low viral load, and receiving antiretroviral therapy can also impact the results of serological assays for recent HIV infection and cause misclassification of recent infection (Hladik et al, 2012;Kirkpatrick et al, 2016;Laeyendecker et al, 2012;Longosz et al, 2014). Although technical advances in HIV recency tests have reduced FRR to 1.7% in LAg-EIA, this percentage is still high and may lead to the overestimation of incidence (Barnighausen et al, 2010;Guy et al, 2009;Shah et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…3D ) using Eqs ( 4 ) and ( 5 ). The genomic assay’s MDRI was estimated to be 420 [361–467] days, which is considerably greater than any previously reported MDRI 12 , 14 – 16 . We compared our model MDRI estimates with that from the proportion of subjects whose GSI values were greater than the cutoff, θ in a one-year bin (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…The Consortium for the Evaluation and Performance of HIV Incidence Assays (CEPHIA) reported MDRIs of serological HIV incidence assays to range from 188 to 333 days with FRRs between 1.3-9.7% 12 , and recently introduced viral load criteria to improve estimates 13 . Other studies 14 – 16 reported FRRs ranging from 0% to 10.2% and MDRIs from 50 to 276 days, and a high misclassification rate in subjects with low CD4 T cell counts 16 , underachieving the optimal performance standards (MDRI ~ 1 year and FRR <1%) 17 . Multi-assay algorithms 13 have been proposed to meet the minimal performance standards (MDRI ~ 4 months and FRR <2%) 17 .…”
Section: Introductionmentioning
confidence: 98%
“…In future work, further refinement of the gp41 and peptide gp41-p1 based immunoassay will be needed and independently evaluated with CEPHIA panels to reach the minimum performance characteristics of an MDRI of >120 days and an FRR <2%, as recommended by the WHO/UNAIDS working group on incidence assays [36]. In addition, factors that may be associated with misclassification of HIV-1 recent infection of HIV-1 including viral loads and subtypes as well as CD4+ cell counts must be evaluated [37]. …”
Section: Discussionmentioning
confidence: 99%